Much Ado About Nothing - "Shakespeare, William" (Sweet cherry publishing: china, 2013)
This play is set in the quiet town of Messina in Sicily, where two pairs of lovers, Benedick and Beatrice, and Claudio and Hero, meet at the house of Leonato, Hero's father and Beatrice's uncle. Benedick and Beatrice engage in a war of witty exchanges, while Claudio and Hero pledge their love for each other and decide to get married. However, in an unexpected turn of events, Hero and Claudio are estranged and Benedick and Beatrice confess their love. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play. It can also be used by teachers as a classroom resource
Keywords: Adaptations Juvenile literature